Lack of Availability and Efficacy of Phase I and Basket Trials for Patients With Gastrointestinal Cancers. (13th December 2019) - Agarwal, Rajiv; Cangemi, Nicholas A; Epstein, Andrew S; Harding, James; Reidy-Lagunes, Diane; Saltz, Leonard B
Abstract: In the modern era of targeted and immune-based therapies, investigator and patient expectations of availability and efficacy in phase I trials have increased. We assessed availability of, and benefit from, early drug development trials, specifically in patients with gastrointestinal cancers. We reviewed computerized referral records of the Early Drug Development Service at our institution to identify patients internally referred from our Gastrointestinal Oncology Service in calendar year 2018. End points were treatment on a trial, 3- and 6-month progression-free survival (PFS), and any tumor shrinkage. Of 394 gastrointestinal cancer patients referred in 2018, 54 enrolled on a trial and 53 (13.5%) were treated (1 withdrew before treatment): 34 on immune-based and 19 on targeted (3 to phase II basket) studies. None of the 52 patients who had exhausted standard therapy achieved 6-month PFS, two (3.8%) met 3-month PFS with tumor growth below Response Evaluation Criteria in Solid Tumors progression at 3 months, and both came off study for progression at 4 months. One patient who was to receive an irinotecan-based regimen as standard therapy instead received irinotecan plus an investigational targeted agent and remained stable for 8 months. No patients achieved any degree of tumor shrinkage. The most common reasons for nonaccrual were lack of available protocol treatment openings and failure to meet eligibility criteria for specific trials. Thus, availability and benefit from investigational treatment in this treatment-refractory gastrointestinal cancer patient population was extremely modest. Expectations regarding both availability and efficacy of phase I investigational therapy in gastrointestinal cancer patients likely exceed what our experience suggests.